Implementation of the Village Fund Allocation (ADD) Management Policy in Kon Tumere Village, Kabawo Sub-district, Muna Regency - Devie S.R.Siwij,; Muh. Hamriadin,; Almen S. Ramaino,; Ismiaty Essing, (Technium Social Sciences Journal, 2024)
Village, Kabawo District, Muna Regency and to find out the factors that influence the Implementation of the Village Fund Allocation Policy (ADD). In this research, data collection was carried out in the following way, collecting data or information through: observation, semi-structured interviews (open interviews), documentation. Data analysis methods include data reduction, data presentation, and drawing conclusions. When viewed from the perspective of achieving objectives, the results of this research can be concluded that the implementation of the Village Fund Allocation Policy in Kontumere Village, Kabawo District, Muna District has not been achieved comprehensively or optimally. This is influenced by several inhibiting factors, namely (1) communication, the inhibiting factor in this communication is socialization to the public regarding the non-existent ADD policy (weakness). This results in the difficulty of inviting community participation in implementing ADD and in monitoring activities (treatment/threats). (2) resources, lack of ability of implementers to operate computers (Weakness), and lack of adequate village income support (Treatment/Threat), (3) Attitude of Implementers, The inhibiting factor in the attitude of implementers is the lack of responsiveness of ADD implementers ( Weakness/Weakness) which considers the ADD policy to be a mere routine policy (Treatment/Threat). (4) Bureaucratic structure, namely the lack of coordination between policy implementers.